Caetana Says No: Women's Stories from a Brazilian Slave Society - Barbosa, Rosana (Labour / Le Travail, 2005)
The article reviews the book, "Caetana Says No: Women's Stories from a Brazilian Slave Society," by Sandra Lauderdale Graham.